Role Modeling-Based Group Guidance for Career Construction of Counseling Students through Socio-Cultural Narratives and Social Presence: A Career Construction Theory Approach - Mudafiatun Isriyah; Weni Kurnia Rahmawati; Herini Kuswardani; Addahri Hafidz Awlawi (Universitas PGRI Yogyakarta, 2026)
This study examines the effectiveness of role-modeling-based group guidance in shaping the careers of Guidance and counseling students through socio-cultural narratives and social presence, within the framework of Career Construction Theory (Savickas). A quantitative approach using Structural Equation Modeling (SEM) was applied to data from 500 students across several universities. The measurement model demonstrated strong reliability and validity (factor loadings > 0.70; AVE > 0.50; CR > 0.70). Structurally, role modeling significantly influenced socio-cultural narratives (β = 0.68, p < 0.001) and social presence (β = 0.59, p < 0.001). Furthermore, socio-cultural narratives (β = 0.42, p < 0.01) and social presence (β = 0.37, p < 0.01) positively predicted career construction, which, in turn, substantially affected the overall effectiveness of group guidance (β = 0.74, p < 0.001). The model explained 63% of the variance in career construction and 55% of the variance in group guidance effectiveness. These findings confirm the importance of socio-cultural and interactional dimensions in enhancing students’ career adaptability and offer practical implications for counselors to design culturally responsive, socially engaging guidance programs that foster career development. Keywords: career construction theory, group guidance, role modeling, socio-cultural narrative, social presence